IMPLEMENTASI METODE THERAPEUTIC COMMUNITY SEBAGAI UPAYA REHABILITASI SOSIAL PENYALAHGUNA NAPZA DI IPWL PUTRA AGUNG MANDIRI KOTA CIREBON - Neng Lilis Dahlia; Syifa Paujiyah; Istiqomah Istiqomah (Peksos: Jurnal Ilmiah Pekerjaan Sosial, 2022)
Drug abuse is currently a worrying problem. Overcoming drug abusers can be done through social rehabilitation. One of the institutions engaged in carrying out social rehabilitation is the Putra Agung Mandiri Institute for Reporting Recipients (IPWL) of Cirebon City. The social rehabilitation method used by IPWL Putra Agung Mandiri is Therapeutic Community. This study aims to determine how to implement the Therapeutic Community method as an effort to rehabilitate drug abusers at IPWL Putra Agung Mandiri, Cirebon City. This study uses qualitative research methods with data collection techniques using interviews and observations. The results of the study indicate that the implementation of the Therapeutic Community method at IPWL Putra Agung Mandiri, Cirebon City has implemented four structures (behavior modification, emotional and psychological, intellectual and spiritual development, and vocational and survival training. In addition, five pillars of the Therapeutic Community method have been implemented with several models of therapy. Therapies that are carried out include physical therapy, psychosocial therapy, mental and spiritual therapy, and livelihood therapy. These therapies are expected to change the behavior of drug abusers in a more positive direction and help to restore their social functioning in the community.